THE POLITICAL-RELIGIOUS IJTIHAD OF NAHDLATUL ULAMA ON THE CONCEPTS OF GUIDED DEMOCRACY, NASAKOM, AND MANIPOL-USDEK (1959-1965) - Firdaus, Abdullah; Harun, Hermanto; Nurjaman, Andri; Witro, Doli; Rasidin, Mhd. (UIN Antasari Banjarmasin, 2024)
Nahdlatul Ulama (NU) has been an Islamic political party since its formal separation from Masyumi in 1952. Following this, the NU party maintained a close relationship with President Soekarno, particularly during the period of Guided Democracy, which was marked by the issuance of the Presidential Decree of 5 July 1959. However, NU's acceptance of Guided Democracy and its components was not immediate but involved a process of religious and political ijtihad (independent reasoning) by NU scholars. In this context, NU’s acceptance and support for the concepts of Guided Democracy, Nasakom (Nationalism, Religion, and Communism), and Manipol-Usdek (the Preamble to the 1945 Constitution) were framed through an Islamic approach. This paper aims to explore and analyze NU's siyasah-diniyyah (religious-political ijtihad) regarding these political concepts. This study employs a qualitative research approach, utilizing the historical method, which involves the stages of heuristics, criticism, interpretation, and historiography. Historical sources relevant to the theme of this research were gathered and analyzed. The findings indicate that the siyasah-diniyyah ijtihad of Nahdlatul Ulama represented support for the ideas and political thought of NU’s clerical leaders in responding to President Soekarno's new political system, particularly Guided Democracy, Nasakom, and Manipol-Usdek. NU’s religious and political stance can be seen in the thoughts of KH. Wahab Chasbullah, the Ro’is Syuriah (Chairman) of PBNU, who accepted Guided Democracy as consistent with Islamic teachings and viewed the 1945 Constitution as an embodiment of the Jakarta Charter. Additionally, the perspective of KH Idham Chalid, Chairman of Tahfidziyah PBNU, is also significant, as he contributed to bridging the gap between Guided Democracy and Islam through the concept of shuro, involving experts and emphasizing full responsibility in decision-making.